Application of 3D food printing in meat production - Vukušić, Tomislava (Array, 2019)
Three-dimensional printing (3D) also known as additive manufacturing (AM) is a developing technology for food manufacturing, which offers novel food products with unique, complex and personalized design geometries, elaborated textures and tailored nutritional content. Today, 3D printing is being applied in military and space food, elderly food and sweets food. This technology offers a potential solution to overcome weaknesses of currently used food techniques, such as lower production efficiency and high manufacturing cost. Main aim of this review is to analyze the potential applications of 3D printing technology for meat processing including 3D printers, meat formulation and several aspects affecting the printability and post processing feasibility of 3D printed meat products.